Who teaches and who learns: unusual spaces and contexts of the XXI century (Research, Society and Development, 2021)
In the light of theorists who constitute an active, meaningful, critical and problematizing education, we seek to dialogue with Jhon Dewey (1859-1952), Decroly (1871–1932), Vigotski (1896-1934), Paulo Freire (1921-1997), meaning of life and its relationship with current education. The theorists offer significant support for our research, being the precursors of their known and widespread theories worldwide. The essay was based on a study with a methodological approach in basic, exploratory and descriptive research with collection procedures and sources of bibliographic information that present in its entire context a bias of the method of dialectical historical materialism, characteristic for presenting phenomena of reciprocal actions, of contradiction, inherent to the phenomenon and the dialectical change that occurs both in the phenomenon and in society. We can say that the conditions of access to hybrid education have been different for each social class and the less favored are the ones who suffer the most, as they are unable to participate in this movement of adaptation and change in the education model, where at this time of health crisis the most used alternative has been remote classes and synchronous and asynchronous activities with the use of technological resources.